2019
DOI: 10.2485/jhtb.28.217
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Porous BMP-6-Loaded Composite Scaffold for Bone Regeneration in Rat Calvarial Bone Defects

Abstract: Biocompatible scaffolding materials play an important role in bone tissue engineering. This study sought to assess the biocompatibility and osteoinductivity of a chitosan (CS)/collagenⅠ(ColI)/multi-walled carbon nanotube (MWCNT) composite scaffold blended with bone morphogenetic protein-6 (BMP-6) and seeded with bone marrow mesenchymal stem cells (BMMSCs). The composite was fabricated using varying quantities of MWCNT to determine the appropriate combination, and combined with BMP-6 by blending and vacuum free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It has been reported that the osteoblast layer of the periosteum is involved in the healing of fractures, and that mechanical stimulation of the periosteum enhances its osteogenic ability [32][33][34]. However, bone tissue regeneration experiments in a skull defect model have shown that the presence of dura is most important in promoting bone regeneration [35][36][37], and it has been shown that the osteoinductive ability of dura as an accelerator for bone regeneration is superior to that of periosteum.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the osteoblast layer of the periosteum is involved in the healing of fractures, and that mechanical stimulation of the periosteum enhances its osteogenic ability [32][33][34]. However, bone tissue regeneration experiments in a skull defect model have shown that the presence of dura is most important in promoting bone regeneration [35][36][37], and it has been shown that the osteoinductive ability of dura as an accelerator for bone regeneration is superior to that of periosteum.…”
Section: Discussionmentioning
confidence: 99%
“…Few preclinical studies have evaluated the osteogenic potential of BMP-6-loaded scaffolds in the CMF region. In one study, rhBMP-6-loaded chitosan/Col/multiwalled carbon nanotubes (MWCNT) scaffolds seeded with MSCs showed increased osteogenic effects in rat cranial CSDs compared to scaffolds lacking the rhBMP-6 . Similarly, nHAp/Gel scaffolds seeded with MSCs enhanced calvarial CSDs in rats compared to scaffolds without the rhBMP-6 …”
Section: Bioactive Factors Incorporated Into Scaffolds Stimulate Cmf ...mentioning
confidence: 99%